APLIKASI ABSEN MURID BERBASIS WEB DENGAN QR CODE PADA SMK SASMITA JAYA 1 - Maulana Riza Fachramdhan; Muhammad Alfin Gio Abidin; Naufal Muzaki; Wasis Haryono (JRIS : Jurnal Rekayasa Informasi Swadharma, 2025)
The attendance system is an important component in monitoring student attendance at school. At SMK Sasmita Jaya 1, the attendance process is still carried out manually using paper forms, which can cause several problems, including delays in recording, data loss, and errors in recapitulation. To overcome these problems, a web-based attendance system was designed and developed using Quick Response (QR) Code technology. The system development utilized the Waterfall model, which consists of four phases: needs analysis, system design, testing, and documentation. Data collection techniques included observation, interviews, and literature studies. The research results are a web-based system that can accommodate various user roles, including admins, teachers, students, homeroom teachers, and principals, with their respective special access rights. The results of the system testing indicate that implementing QR Codes in the attendance process increases efficiency, reduces input errors, and simplifies real-time reporting. Additionally, this system promotes transparency and accountability in managing student attendance and has the potential to be further enhanced with additional security features, such as tokenization and location tracking.Sistem absensi merupakan komponen penting dalam memantau kehadiran siswa di sekolah. Di SMK Sasmita Jaya 1, proses absensi masih dilakukan secara manual menggunakan formulir kertas, yang dapat menimbulkan beberapa masalah seperti keterlambatan pencatatan, kehilangan data, dan kesalahan rekapitulasi. Untuk mengatasi masalah tersebut, dirancang dan dikembangkan sistem absensi berbasis web menggunakan teknologi Quick Response (QR) Code. Pengembangan sistem menggunakan model Waterfall yang terdiri dari analisis kebutuhan, desain sistem, pengujian, dan fase dokumentasi. Teknik pengumpulan data meliputi observasi, wawancara, dan studi pustaka. Hasil penelitian berupa Sistem berbasis web yang dapat mengakomodasi berbagai peran pengguna termasuk admin, guru, siswa, wali kelas, dan kepala sekolah dengan hak akses khusus masing-masing. Hasil pengujian sistem menunjukkan bahwa penerapan QR Code dalam proses absensi meningkatkan efisiensi, mengurangi kesalahan input, dan menyederhanakan pembuatan laporan secara real-time.